Availability of Provider Information About Zika Virus and Perinatal Risks on State Health Department Websites [21O]. (May 2017) - Gray, Jordan; Page-Ramsey, Sarah M.; Ireland, Kayla; Rivera, Joshua; Rodriguez, Emma; Ramsey, Patrick S.
Abstract : INTRODUCTION: Zika virus is an emerging health threat in pregnant women. It is important that obstetric healthcare providers can access up-to-date information about Zika testing, resources, and cases. Our objective was to evaluate the availability of provider-level information about Zika virus on state and US territory health department websites. METHODS: We reviewed each U.S. state, District of Columbia, and US territory (Puerto Rico, Guam, US Virgin Islands, American Samoa, North Marianas Islands) health department websites and abstracted provider-level information on Zika testing, testing forms, links to Center for Disease Control (CDC) publications, blood bank/donation guidelines, local cases, and US Zika pregnancy registry information. In cases where information about Zika virus did not appear immediately on the main webpage, an internal search of the site using the term "Zika" was performed. RESULTS: Provider-level information about Zika virus was found on 82.1% of 56 websites reviewed. Of those sites with information, information was more common on state websites (88.2%) than on territory sites (20.0%). Information available included Zika testing information (76.9%), access to in-state testing (73.1%), testing forms (59.6%), links to CDC publications (80.8%), blood bank/donation guidelines (25.0%), local cases (76.9%), and US Zika pregnancy registry information (32.7%). CONCLUSION: Provider-level information about Zika virus is available on most state, but not US territory websites. Testing information, CDC publications, blood bank/donation guidelines, local cases, and US Zika pregnancy registry information are not consistently available. State and territory sites should include such information to assist healthcare providers in optimal care of the obstetric population.